Integrated Literacy Program in the "Kampus Mengajar" Policy in Elementary Schools - Novayanti Sopia Rukmana; Febrianto Syam; Dyan Paramitha Darmayanti; Darman Manda; Nur Fadhilah Umar (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Literacy is a crucial factor in enhancing education quality, particularly in the digital era. However, data from PIRLS 2021 reveals that Indonesian students, including those in Makassar City, still demonstrate low literacy levels. This study aims to analyze the implementation and effectiveness of an integrated literacy program within the Teaching Campus policy at UPT SPF SD Inpres Tello Baru. Using a qualitative approach with a pre-test and post-test design, the study involved 62 students from grades 4 and 5, as well as school principals, teachers, library staff, and Teaching Campus participants. The program consisted of three components: reading clinics, literacy fun games, and library revitalization. The findings indicate a significant improvement in students’ literacy. The reading clinic enhanced fluent reading in 68.2% of students receiving intensive support. Participation in literacy activities rose to 72.5% through fun games, while daily library visits increased from 5–8 to 15–20 students, with longer durations. Reading comprehension scores improved by 42%, with 85% of students achieving greater fluency and 75% showing better retelling skills. Despite challenges such as limited time and varying student abilities, the program’s success was driven by collaboration among Teaching Campus participants, school staff, and students. The results confirm that a holistic literacy approach—combining personalized guidance, interactive learning, and infrastructure enhancement—can effectively strengthen literacy culture in primary schools.